2017
DOI: 10.1155/2017/7868954
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcomes in Critically Ill Patients with Human Immunodeficiency Virus Infection in the Era of Combination Antiretroviral Therapy

Abstract: Purpose. The impact of critical illness on survival of HIV-infected patients in the era of antiretroviral therapy remains uncertain. We describe the epidemiology of critical illness in this population and identify predictors of mortality. Materials and Methods. Retrospective cohort of HIV-infected patients was admitted to intensive care from 2002 to 2014. Patient sociodemographics, comorbidities, case-mix, illness severity, and 30-day mortality were captured. Multivariable Cox regression analyses were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 47 publications
6
12
1
Order By: Relevance
“…However, despite that proportion of patients receiving HAART is increasing, only 54.8% of our patients were under HAART at admission. These data are comparable to those reported by other countries from our region, 18,28,33 and the level in Spain is higher than in the studies published from countries such as Australia, Brazil, Taiwan and China (in which less than 40% of patients received ART), 22,26,27,29 but far from the 71% reported in the USA by Akgün et al 20 This variability in the percentage of patients who receive ART is reflected in their CD4 T-lymphocyte counts at admission. Among our patients, the median was 167 cells/mm 3 (53.5, 414.0); in studies with a lower percentage of patients receiving ART, the CD4 count is lower, even falling below 50 cells/mm 3 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, despite that proportion of patients receiving HAART is increasing, only 54.8% of our patients were under HAART at admission. These data are comparable to those reported by other countries from our region, 18,28,33 and the level in Spain is higher than in the studies published from countries such as Australia, Brazil, Taiwan and China (in which less than 40% of patients received ART), 22,26,27,29 but far from the 71% reported in the USA by Akgün et al 20 This variability in the percentage of patients who receive ART is reflected in their CD4 T-lymphocyte counts at admission. Among our patients, the median was 167 cells/mm 3 (53.5, 414.0); in studies with a lower percentage of patients receiving ART, the CD4 count is lower, even falling below 50 cells/mm 3 .…”
Section: Discussionsupporting
confidence: 87%
“…These data are similar to those recently published describing industrialized countries. 22,28,33 However, in the studies by Chiang et al and Xiao et al, the clinical course of the disease was much shorter (less than a year), with a high percentage of diagnoses during admission (approximately 50%). 26,29 At present, it is widely currently recommended that HAART be administered to all HIV-infected patients, regardless of immunovirological profile or symptoms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…With regard to serum albumin concentration, some studies showed that low levels were a nonsignificant predictor of ICU mortality . A study by Morris et al reported that higher levels of serum albumin were significantly associated with an increased odds of survival .…”
Section: Discussionmentioning
confidence: 99%
“…The spectacular improvement of life expectancy in cART-treated patients offers long-term perspectives that justify maximizing the level of supportive care when indicated. Invasive mechanical ventilation (MV, 40-50% of all admissions), vasopressors (15-30%), and renal replacement therapy for AKI (8-15%) are now used as frequently in seropositive individuals as in the general ICU population [5,7,24,33,43,44], with comparable prognoses including in patients at high risk of death such as those admitted following cardiac arrest or with the acute respiratory distress syndrome (ARDS) [45,46]. Last-resort veno-venous or veno-arterial extracorporeal membrane oxygenation can be discussed in selected patients, with auspicious results in published reports [47,48].…”
Section: Similarities Between Critically Ill Hiv-infected and Seronegmentioning
confidence: 99%